2007
DOI: 10.1158/1078-0432.ccr-06-3043
|View full text |Cite
|
Sign up to set email alerts
|

KRASMutation Is an Important Predictor of Resistance to Therapy with Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors in Non–Small-Cell Lung Cancer

Abstract: Purpose: EGFR gene mutations and increased EGFR copy number have been associated with favorable response to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (EGFR-TKI) in patients with non^small-cell lung cancer (NSCLC). In contrast, KRAS mutation has been shown to predict poor response to such therapy. We tested the utility of combinations of these three markers in predicting response and survival in patients with NSCLC treated with EGFR-TKIs. Experimental Design: Patients with advanced NSCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
370
1
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 567 publications
(397 citation statements)
references
References 32 publications
17
370
1
9
Order By: Relevance
“…Pao et al (2005b) first suggested that patients with NSCLC whose tumors harbor mutations are resistant to EGFR TKI. To date, among 75 NSCLC patients harboring KRAS mutations who were treated with TKIs (Pao et al, 2005b;Hirsch et al, 2006;Massarelli et al, 2007;Miller et al, 2008;Zhu et al, 2008), only one patient has been reported to respond (Zhu et al, 2008). Interestingly, this patient's tumor also had an EGFR gene amplification.…”
Section: Genetic Polymorphisms and Egfr-targeted Drugsmentioning
confidence: 95%
“…Pao et al (2005b) first suggested that patients with NSCLC whose tumors harbor mutations are resistant to EGFR TKI. To date, among 75 NSCLC patients harboring KRAS mutations who were treated with TKIs (Pao et al, 2005b;Hirsch et al, 2006;Massarelli et al, 2007;Miller et al, 2008;Zhu et al, 2008), only one patient has been reported to respond (Zhu et al, 2008). Interestingly, this patient's tumor also had an EGFR gene amplification.…”
Section: Genetic Polymorphisms and Egfr-targeted Drugsmentioning
confidence: 95%
“…Activating mutations in EGFR and less commonly ErbB2 occur in lung cancer and activate the Ras/MAPK pathway. However, mutational activation of KRAS is seen in lung cancers as well and can render these tumors resistant to ErbB receptor targeting TKIs [179]. Such a phenomenon is seen in approximately 14 % of lung adenocarcinomas [155,180].…”
Section: Resistance To Targeted Therapymentioning
confidence: 99%
“…Earlier studies indicated that KRAS mutant NSCLC patients fail to benefit either from adjuvant chemotherapy or from EGFR inhibitors [7,16,[27][28][29]. Lack of EGFR mutation status of the KRAS WT patients represents a major limitation of our study (i.e.…”
Section: Discussionmentioning
confidence: 91%
“…In the western world, in patients with lung adenocarcinoma, KRAS mutations are the most common (18-38% of cases), followed by mutations in the epidermal growth factor receptor (EGFR) gene (5-15% of cases) [5][6][7][8]. In Hungary, the incidence of KRAS mutation in lung adenocarcinoma is 29.5% (based on the analysis of 6250 patients; unpublished data).…”
Section: Introductionmentioning
confidence: 99%